Industry views on water resources planning planning methods – prospects for change in England and Wales - Turner, Sean W. D.; Jeffrey, Paul (Wiley, 2015)
This paper describes a qualitative study of practitioner perspectives on regulated water resources planning practice in England and Wales. The study focuses on strengths and weaknesses of existing practice and the case for change towards a risk-based approach informed by stochastic modelling assessments. In-depth, structured interviews were conducted to capture the views of planners, regulators and consultants closely involved in the planning process. We found broad agreement that the existing water availability assessment methods are fallible; they lack transparency, are often highly subjective and may fail to adequately expose problems of resilience. While most practitioners believe these issues warrant a more detailed examination of risk in the planning process, few believe there is a strong case for a fundamental shift towards risk-based planning informed by stochastic modelling assessments. The study identifies perceived business risks associated with change and exposes widespread scepticism of stochastic methods.
Keywords: modelling; risk assessment; uncertainty analysis; water industry; water resources; water supply; water supply and demand